Global Advertising Messages for Cosmopolitan Consumers to Promote Green Buying Behavior: A Cross-country Investigation - Graça, Sandra S. (Archīum Ateneo, 2024)
This study empirically tests a conceptual model of the impact of cosmopolitan orientation on green buying behavior in the U.S., Brazil, and Germany. The following were examined: relationships between a consumer’s global versus local identity, cosmopolitan orientation, and preference for a global framing of advertising messages for a green product, as well as the influence of a consumer’s cosmopolitan orientation on pro-environmental factors that ultimately contribute to greater intention and willingness to purchase green products. Data were collected through a self-administered online survey. Correlations and regression analysis were used to analyze the data, and structural equation modeling was used to test the hypothesized model in the study. Findings indicate that global identity and framing of advertising are positively linked to cosmopolitan orientation across all three countries. Results demonstrate the role of cosmopolitan orientation in influencing a consumer’s knowledge and concern about the environment, positive attitude toward buying green products, and the perceived effectiveness of their pro-environmental purchasing behavior. In turn, these mediating factors foster green buying behavior (GBB) in all three countries with a few distinctions. The findings highlight the importance of using global framing messages when advertising green products and services to an increasingly cosmopolitan-oriented consumer base. In all three countries, communication strategies should focus on messages that link cosmopolitan consumers to the rest of the world and educate consumers about the state of the environment and the positive difference that consumers can make when adopting eco-friendly products.